SUSTAINABILITY REPORTING AND CORPORATE ACCOUNTABILITY IN THE GREEN ECONOMY IN ENERGY SECTOR: ECONOMIC AND POLITICAL PERSPECTIVES - Tabitha, Abigail (JURNAL DARMA AGUNG, 2025)
This study aims to explore sustainability reporting and corporate accountability in the context of a green economy in the energy sector through economic and political perspectives. In the era of transition towards a green economy, the energy sector has a strategic role in reducing environmental impacts while meeting global energy needs. Sustainability reporting is an important instrument to measure corporate social and environmental responsibility, as well as transparency in their operations. This study uses a qualitative approach with a descriptive method that focuses on literature studies from various previous studies related to sustainability reporting and corporate accountability. Through a study of existing literature, this study found that economic regulations, political pressure, and public policy play an important role in shaping sustainability reporting standards in the energy sector. In addition, political and economic dynamics, including industry lobbying and pressure from international organizations, also influence the effectiveness of corporate accountability in implementing sustainability. The results of this study are expected to contribute to the development of better policies to improve corporate accountability in the green economy in the energy sector.